2018
DOI: 10.1002/bmc.4347
|View full text |Cite
|
Sign up to set email alerts
|

Novel determination of sofosbuvir and velpatasvir in human plasma by UPLC–MS/MS method: Application to a bioequivalence study

Abstract: A novel and sensitive LC-MS/MS method was developed, optimized and validated for quantification of sofosbuvir (SOF) and velpatasvir (VEL) in human plasma using ledipasvir as an internal standard (IS). Sample preparation was done using acetonitrile for precipitation of plasma proteins. Chromatographic analysis was done on an Acquity UPLC BEH C column using 0.1% formic acid and acetonitrile as a mobile phase. The Xevo TQD LC-MS/MS system was run with electrospray ionization mode. The developed method was optimiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…A mobile phase composed of ACN and FA was frequently used in most of the reported UPLC methods for the analysis of sofosbuvir due to its superior separation characteristics (Notari et al, 2018; Pan et al, 2016; Rezk et al, 2015; Rezk et al, 2018; Rezk, Basalious, & Amin, 2016; Rezk, Bendas, et al, 2016; Semreen et al, 2019; Shi et al, 2015). This mixture eluted the analytes and IS in a narrow range, which in turn reflects on the compensation for matrix effects (Rezk et al, 2015; Rezk, Basalious, & Amin, 2016) and the fluctuation in ionization of MS analysis, with a reduction in the total time needed for the analysis (Rezk et al, 2018).…”
Section: Uplc Based Methods For the Determination Of Sofosbuvirmentioning
confidence: 99%
See 2 more Smart Citations
“…A mobile phase composed of ACN and FA was frequently used in most of the reported UPLC methods for the analysis of sofosbuvir due to its superior separation characteristics (Notari et al, 2018; Pan et al, 2016; Rezk et al, 2015; Rezk et al, 2018; Rezk, Basalious, & Amin, 2016; Rezk, Bendas, et al, 2016; Semreen et al, 2019; Shi et al, 2015). This mixture eluted the analytes and IS in a narrow range, which in turn reflects on the compensation for matrix effects (Rezk et al, 2015; Rezk, Basalious, & Amin, 2016) and the fluctuation in ionization of MS analysis, with a reduction in the total time needed for the analysis (Rezk et al, 2018).…”
Section: Uplc Based Methods For the Determination Of Sofosbuvirmentioning
confidence: 99%
“…The use of isocratic elution allows omitting the equilibration step after finishing gradient (Rezk et al, 2018), and the use of gradient elution was found to compensate for the carry‐over problems in the simultaneous determination of sofosbuvir, GS‐331007, grazoprevir, ledipasvir, simeprevir, daclatasvir, elbasvir, and velpatasvir (van Seyen et al, 2019).…”
Section: Uplc Based Methods For the Determination Of Sofosbuvirmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature review discloses that a very few spectroscopic, [7,8] LC-MS/MS, [9] and high performance liquid chromatographic techniques [10][11][12][13][14][15][16] have been reported for the estimation of VXR, SFR, and VLR. Based on the reported HPLC methods, there is a need to develop a rapid, sensitive reversed-phase-UPLC method for simultaneous estimation of VXR, SFR, and VLR in bulk and formulations.…”
Section: Original Articlementioning
confidence: 99%
“…After a thorough literature survey, it is observed that there are many analytical methods reported for analysis of SOF and VEL, either single or in combination, but no SIM-HPTLC method was found for combination. The reported methods of SOF combination with VEL include analytical methods like LC-MS/MS, [1] HPLC, [2][3][4][5] UPLC MS/MS [6] and UPLC. [7]…”
Section: Abstract a R T I C L E I N F Omentioning
confidence: 99%